Infância, autonomia e pós-estruturalismo : alguns diálogos - Barbosa, Rita de Cássia Moreno (Universidade Federal de São Carlos, 2015)
The central objective of this research was to discuss, within the sociology of childhood, how the children´s action has been designed and channeled. From a literature review of some reputable authors, namely: Jens Qvortrup, Leena Alanen, Mayall, William Corsaro, Allison James, Chris Jenks and Alan Prout; traveled briefly the main theoretical aspects that make up the field of New Sociology of Childhood seeking clues about how they understand the role of the child within the social fabric. Our aim was to show how the representation of incompleteness and dependence in which we insist glimpse children, linked to social and educational expectations of building an ideal subject (read disciplined, rational and univocal) has influenced directly in their / our shares and relationships. All these theoretical approaches have in common the desire to observe the child autonomously, that is, as an independent analytical category. However, as we saw in this study and develop the concept of autonomous child has been appropriated by different currents in very different ways and even controversial. For this reason, we look back with greater emphasis on post-critical theoretical approaches to the extent that most of the authors understand that the concept of autonomy is insufficient to discuss social action of children. Found in the post-structuralism - theoretical model that drove the post-critical theory - theoretical and methodological elements to reconsider the role of children from the study of relations. This line of thought seems promising in that it focuses on the study not of static subjects, but the relationship between them. Our aim was to contribute to provide evidence and discussions of post-structuralist theoretical perspective, taking it, not just as a tool for a conceptual analysis of the major issues that affect early childhood education; as well as discussing the practical feasibility of a post-structuralist education.
Keywords: Sociologia da Infância; Pós-estruturalismo; Autonomia; Sociology of childhood; Post-structuralism; Autonomy; CIENCIAS HUMANAS::EDUCACAO